THE SPECIFIC CHARACTER OF PEDAGOGICAL HIGHER EDUCATION IN THE CONDITIONS OF PEDAGOGICAL INSTITUTES REORGANIZATION - Alexander N. Novikov; Maria S. Novikova (Moscow Polytechnic University, 2022)
The specificity of pedagogical higher education lies first of all in the organization of the learning process in the pedagogical institute, and in the specificity of students' and teachers' environment; the interaction "teacher - student"; research and education results; teachers' status; students' mentality; reflection. In the condition of pedagogical university reorganization, the main task is to preserve the established traditions expressing this particular specificity.